Torque-angle-velocity Relationships and Muscle Performance of Professional and Youth Soccer Players - Mazuquin, B. F.; Dela Bela, L. F.; Pelegrinelli, A. R. M.; Dias, J.M.; Carregaro, R. L.; Moura, F. A.; Selfe, J.; Richards, J.; Brown, L. E.; Cardoso, J. R. (International Journal of Sports Medicine, 2016)
Soccer matches consist of a variety of different activities, including repeated sprints. Time to attain velocity (TTAV), load range (LR) and the torque-angle-velocity relationship (TAV3D) represent an important measurement of muscle performance, however there are few related studies. The aim of this study was to compare these outcomes between soccer players of different age category. 17 professional (PRO) and 17 under-17 (U17) soccer players were assessed for concentric knee flexion/extension at 60, 120 and 300°/s. For the extensor muscles, differences were found in favor of the U17 group for TTAV and LR outcomes at 120°/s, however, the PRO group maintained higher torques in both movement directions in comparison to the U17 in TAV3D evaluation. These results suggest that muscle performance of the PRO group is more efficient than the U17 group.
Keywords: biomechanics; isokinetic; knee; 3D surface mapping